Migrant Labor Markets And The Welfare of Rural Households In The Developing World : Evidence From China - De Brauw, Alan (The World Bank, 2008)
In this paper, the authors examine the impact of reductions in barriers to migration on the consumption of rural households in China. The authors find that increased migration from rural villages leads to significant increases in consumption per capita, and that this effect is stronger for poorer households within villages. Household income per capita and non-durable consumption per capita both increase with out-migration, and increase more for poorer households. The authors also establish a causal relationship between increased out-migration and investment in housing and durable goods assets, and these effects are also stronger for poorer households. The authors do not find robust evidence, however, to support a connection between increased migration and investment in productive activity. Instead, increased migration is associated with two significant changes for poorer households: increases both in the total labor supplied to productive activities and in the land per capita managed by the household. In examining the effect of migration, we pay considerable attention to developing and examining our identification strategy